Occurrence of Escherichia coli harbouring stx genes in popiah, a Malaysian street food - Nillian, Elexson; F. N., Nik Yuhanis; Tan, Malcolm Turk Hsern; C. Y., New; Chang, W. S.; Ubong, A.; Kuan, Chee Hao; Loo, Yuet Ying; Thung, Tze Young; Radu, Son (Rynnye Lyan Resources, 2017)
Irrespective of its health effects, street foods are very popular with the consumers. The main purpose of this research was to study the biosafety of Escherichia coli in popiah, a Malaysian street food sold at a roadside food stall and a restaurant in Sri Serdang, Selangor, Malaysia, using the combination of the most probable number (MPN)-Polymerase Chain Reaction (PCR) assay-plating on Eosin Methylene Blue (EMB) agar methods. Using these biomolecular methods, E. coli was detected in 12/15 (80%) and 11/15 (73%) of the collected samples from the roadside food stall and the restaurant respectively. The incidence of stx virulence-associated genes was detected in 1/15 (7%) among the E. coli isolated from samples taken from the roadside food stall while the E. coli isolated from the restaurant was 3/15 (20%). The density of E. coli ranged from <3 to >1100 MPN/g and the density of E. coli positive with stx genes was <3 to 53 MPN /g in samples from both the roadside food stall and the restaurant. The presence of the stx-positive E. coli in popiah are significant to risk assessments of food and epidemiological studies. Therefore, from the information obtained in this study, it is obvious that the screening for STEC markers in food samples would be useful for food safety survey.